ÐŸÑ€Ð¾Ð½Ð¸Ñ†Ð°ÐµÐ¼Ð¾ÑÑ‚ÑŒ Ð¼ÐµÐ¼Ð±Ñ€Ð°Ð½ Ð¾Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ð¸ ÑÐ¼Ð±Ñ€Ð¸Ð¾Ð½Ð¾Ð² Ð¼Ñ‹ÑˆÐ¸ Ð´Ð»Ñ Ð¼Ð¾Ð»ÐµÐºÑƒÐ» 1,2-Ð¿Ñ€Ð¾Ð¿Ð°Ð½Ð´Ð¸Ð¾Ð»Ð° Ð¸ Ð¿Ð¾Ð²Ñ€ÐµÐ¶Ð´Ð°ÑŽÑ‰ÐµÐµ Ð´ÐµÐ¹ÑÑ‚Ð²Ð¸Ðµ ÐµÐ³Ð¾ ÐºÐ¾Ð½Ñ†ÐµÐ½Ñ‚Ñ€Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… Ñ€Ð°ÑÑ‚Ð²Ð¾Ñ€Ð¾Ð² - Pishko, O. V.; Smolyaninova, E. I.; Kovalenko, I. F.; Rozanov, L. F. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
The permeability coefficients of plasma membranes of oocytes, 1-, 2- and 8-cell murine embryos for 1,2-propane diol (1,2-PD) and water molecules were determined. The fertilisation and embryo development stage were shown as not affecting the transport characteristics of cell membranes.